0466 Living Alone as a Predictor of Symptom Change During Cognitive Behavioral Therapy for Insomnia. (25th May 2022) - Tutek, Joshua; Gumport, Nicole; Dietch, Jessee; Tully, Isabelle; Simpson, Norah; Manber, Rachel
Abstract: Introduction: Interpersonal factors have implications for sleep quality. Research has begun to explore how such factors may play a role in cognitive behavioral therapy for insomnia (CBTI). This study investigated whether living alone predicts reductions in insomnia severity and sleep-related daytime impairment across the first two months of treatment in a trial of CBTI. Methods: Participants were 224 middle-to-older-aged adults with insomnia (166 women, M age = 63.16) enrolled in the ongoing Randomized Controlled Study on Effectiveness of Stepped-Care Sleep Therapy (RESTING). All study participants received CBTI, delivered either via a therapist or a validated software program. At baseline, participants indicated whether they lived alone or with at least one other person. The Insomnia Severity Index (ISI) and PROMIS Sleep-Related Impairment (SRI) short form were administered at baseline and two months after starting treatment. Mixed effects models assessed whether living alone predicted reduction in symptoms across the first two months of CBTI. Results: Across the total sample, ISI scores decreased from baseline to two months (β=-3.52, SE=0.35, p<.001, 95% CI=-4.20, -2.84). Living alone was not associated with baseline ISI scores nor change in ISI score. A reduction in PROMIS SRI score was also observed in the total sample from baseline to two months (β=-4.18, SE=0.50, p<.001, 95% CI=-5.15, -3.21). Living alone was not associated with baseline SRI score, but it did predict reduction in SRI score (β=-3.23, SE=0.88, p=.001, 95% CI=1.31, 5.15). Participants living alone displayed less reduction in SRI compared to those living with at least one other person. Conclusion: Participants undergoing CBTI who live alone experienced reduction in insomnia severity over the course of treatment, but they displayed less improvement in daytime sequalae of poor sleep compared to those living with others. Future studies should further explore how living status contributes to insomnia treatment response across both nighttime and daytime sleep symptomology. Regular engagement with others living in the home may be important for insomnia treatment to translate into perceived functional improvements during the day. Support (If Any): 1R01AG057500